New erbium-doped fiber laser with a double tunable bandpass filter - Sellami , Ali; Al-Khateeb, Khalid A. Saeed; Billoui, Bouzid (2008)
A new configuration for an erbium-doped fiber laser is reported. It incorporates a linear cavity with fiber loopback and a tunable bandpass filter (TBF). This configuration suppresses the amplified spontaneous emission and achieves a highly stable output power of more than 18 dBm at 1560 nm. A standard spectrum is obtained with TBF adjustment.